The effect of fibre treatment on water absorption and mechanical properties of buri palm (Corypha utan) fibre reinforced epoxy composites - M., Zalinawati; Siregar, J. P.; Tezara, C.; Sazali, N.; Jaafar, J.; Oumer, A. N.; M. Hamdan, M. H. (Universiti Malaysia Pahang Publisher, 2020)
Over the past century, there has been a dramatic increase in natural fibre composites in which natural fibre has served as reinforcement in polymer. However, the existence of moisture and defects in natural fibres has impacted the mechanical and physical properties of natural fibre polymer composites. The main objective of this study is to fabricate the buri palm fibre reinforced epoxy composite and evaluate the effects of fibre treatment on water absorption and tensile properties. The buri palm fibre were treated by using 5 wt.% NaOH for 24 h and the laminated composite of untreated and treated four-layer and five layer fibres were fabricated via hand lay-up process. The tensile specimens are prepared according to the ASTM D638 standard and the water absorption experiment was conducted by immersing the specimen in distilled water at room temperature until it reached the saturated moisture absorption. The results revealed that the percentage of moisture uptake was reduced to 69% and 95% in treated four-layer and fivelayer sequences. It is observed that the thickness swelling of the composite increased with the increase of sequence layering, while the thickness swelling decreased with treated fibre. Alkali treatment affected the properties of buri palm fibre which improved the interfacial bonding between the fibre and epoxy matrix for better tensile properties and reduced water absorption. Finally, morphology examinations were carried out to analyse the fracture behaviour and fibre failure on the tensile test specimen by using microscope analysis.